A Modified Staged Surgical Intervention for Blepharophimosis-Ptosis-Epicanthus Inversus Syndrome. Issue 4 (April 2015) - Song, Xin; Jia, Renbing; Zhu, Huimin; Zhou, Yixiong; Sun, Ying; Lin, Ming; Fu, Yao; Li, Jin; Li, Zhengkang; Lu, Linna; Shen, Yundun; Ge, Shengfang; et al.
<x xml:space="preserve">Abstract</x> Background Blepharophimosis-ptosis-epicanthus inversus syndrome (BPES) is a rare autosomal dominant condition characterized by typical eyelid malformations that include blepharophimosis, ptosis, epicanthus inversus, and telecanthus. Methods We retrospectively reviewed 125 consecutive BPES patients who underwent staged surgical intervention from July 2003 to December 2011. All patients underwent initial medial and lateral canthoplasties, followed by blephroptosis correction 6 to 12 months afterward. The parameters that were studied included horizontal palpebral fissure length (PFL), vertical interpalpebral fissure height, inner intercanthal distance (IICD), the ratio of IICD to PFL, and frontalis function (FF). Facial photographs were taken preoperatively and postoperatively. Paired and group t tests were used for statistical analysis to evaluate surgical outcomes. Results After consecutive operations, the mean PFL increased from 19.5 to 25.7 mm (mean difference, 6.2 mm; P < 0.01). The mean interpalpebral fissure height increased from 3.4 to 8.5 mm (mean difference, 5.1 mm; P < 0.01). The mean IICD decreased from 38.0 to 30.9 mm (mean difference, 7.1 mm; P < 0.01). The mean FF was 7.3 mm for BPES patients approximately 5 years old and 10.4 mm for patients approximately 7 years old. There was no difference between children who underwent muscle flap suspension and healthy children of the same age (P > 0.05). Conclusions The modified staged surgical intervention, including Y-V flap, von Ammon, and frontalis muscle flap suspension, provided effective results both in function and cosmesis for BPES. The FF was not weakened by surgery.